ANALISIS KESESUAIAN DAN DAYA DUKUNG LINGKUNGAN PERAIRAN TERHADAP PENGEMBANGAN BUDIDAYA RUMPUT LAUT Eucheuma cottonii DI PESISIR KECAMATAN SUPPA KABUPATEN PINRANG - Damis, Damis (Universitas Negeri Makassar, 2018)
This study aims to determine the suitability of land and carrying capacity for seaweed farming in the coastal area of Suppa District Pinrang Regency, assess the feasibility of seaweed cultivation development; identify factors of strengths, weaknesses, opportunities, and threats that affect the development of seaweed cultivation area; formulating a seaweed cultivation development strategy The method used is: spatial data analysis with Geogerafis Information System method, SWOT analysis to determine the strategy of seaweed cultivation area development. The results showed that the width of land suitability for seaweed cultivation based on land suitability map was appropriate (S) ± 578,57 hectare and not appropriate (N) ± 759,68 hectare, while the carrying capacity of land for seaweed cultivation is ± 173,571 hectare. Priority of Seaweed Development Strategy based on the results of the analysis, determined the eight best strategies of seaweed cultivation business development 1. Develop a cultivation processing, 2. Provide training gradually. 3. Provide gradual counseling, 4. Optimize existing production capacity, 5. Expand the cultivation area, 6. Optimize production, 7. Increased access to capital, 8. Expand and maintain network marketing.